Iman sebagai Praktik Sosial: Penguatan Budaya Religius melalui Dakwah bil Hal di Pondok Pesantren Progresif Semarang - Miftakhul Janah; Ariana Suryorini; Lukmanul Hakim; Dedy Susanto (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2026)
This study examines the implementation of dakwah bil hal at Pondok Pesantren Progresif Fathimah Al-Amin in Ngaliyan, Semarang, and its role in strengthening students’ religious culture. Dakwah bil hal is understood as a form of preaching based on exemplary conduct, habituation, and concrete practices that internalize Islamic values in daily life. Using a qualitative approach involving participant observation, in-depth interviews, and document analysis, the study identifies three core strategies: teachers’ moral exemplarity, institutionalized ritual practices, and social interactions that foster collective religious awareness. These strategies contribute to the formation of disciplined, responsible, and morally grounded students. The pesantren also integrates spiritual values into a life-skills based curriculum, linking religious formation with social preparedness. Theoretically, this study enriches contemporary dakwah discourse by emphasizing lived practice as a mechanism of value internalization. Practically, it offers a contextual and sustainable model of character formation relevant to modern educational challenges.